2020
DOI: 10.1111/vox.12975
|View full text |Cite
|
Sign up to set email alerts
|

Noncompliance to blood donor selection criteria by men who have sex with men – Complidon 2017, France

Abstract: Background and objectives In France, blood donation deferral for men who have sex with men (MSM) was reduced from permanent to 12 months in July 2016. Assessing noncompliance (rate and reasons) with this criterion is important to maintain a high level of viral safety in blood products. Materials and methods An anonymous online survey (Complidon) of a sample of blood donors was conducted in 2017. Data were post-stratified to be representative of all those who donated blood between July 2016 and December 2017. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 18 publications
1
15
2
Order By: Relevance
“…To evaluate BD compliance with the main selection criteria, an anonymous online survey (Complidon) was undertaken in from September to November 2017 with 108,000 BDs in France. This study showed that the overall noncompliance rate was 3.6% of BDs who did not report at least one deferral criterion regarding sexually transmitted infections, drug use, or tattoo/piercing upon their last donation 11 . Regarding infectious risks, 0.73% of male donors reported sex between men within the last 12 months before donation, and 1.9% of BDs reported a multiple sexual partnership 11 .…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations
“…To evaluate BD compliance with the main selection criteria, an anonymous online survey (Complidon) was undertaken in from September to November 2017 with 108,000 BDs in France. This study showed that the overall noncompliance rate was 3.6% of BDs who did not report at least one deferral criterion regarding sexually transmitted infections, drug use, or tattoo/piercing upon their last donation 11 . Regarding infectious risks, 0.73% of male donors reported sex between men within the last 12 months before donation, and 1.9% of BDs reported a multiple sexual partnership 11 .…”
Section: Introductionmentioning
confidence: 81%
“…In addition, as shown by Complidon, MSM might not reveal their true mode of HIV transmission during the postdonation interview for various reasons. They might report either no risk factors or make up another more accepted risk factor 11 . Using HIV sequences from a French cohort of primary HIV infections (ANRS CO6 PRIMO cohort) with detailed sociodemoepidemiological data and from French BDs diagnosed with HIV‐1 over 16 years of surveillance, we applied a network inference approach to estimate risk factors in BDs who did not report their true potential mode of contamination during postdonation interview or in BDs for whom no data were available.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other countries are also considering ways to permit low‐risk MSM to donate and are involved in extensive research and consultation to find the best way to balance safety, sufficiency, and fairness 15–18 . Further research is required to identify criteria to better distinguish between low‐ and high‐risk activities in ways that lend themselves to donor screening questions.…”
Section: Discussionmentioning
confidence: 99%